Report on the agricultural survey of Northern region of Nigeria - Food and Agricultural Organisation; International Cooperation Administration (Kaduna, Nigeria FAO / ICA, 1960)
This is the report of an Agricultural Survey of the Northern Region of Nigeria, carried out by a team of thirteen members, seven of whom were nominated by the Food and Agricultural Organization of the U.N. and six by the U.S. ICA.
osc 30/10/2019
Arch
Keywords: Agricultural economics; Nigeria